Angiotensin‐converting enzyme 2 deficiency accelerates and angiotensin 1‐7 restores age‐related muscle weakness in mice. Issue 5 (11th September 2018) - Takeshita, Hikari; Yamamoto, Koichi; Nozato, Satoko; Takeda, Masao; Fukada, So‐ichiro; Inagaki, Tadakatsu; Tsuchimochi, Hirotsugu; Shirai, Mikiyasu; Nozato, Yoichi; Fujimoto, Taku; Imaizumi, Yuki; Yokoyama, Serina; et al.
Abstract: Background: A pharmacologic strategy for age‐related muscle weakness is desired to improve mortality and disability in the elderly. Angiotensin‐converting enzyme 2 (ACE2) cleaves angiotensin II into angiotensin 1‐7, a peptide known to protect against acute and chronic skeletal muscle injury in rodents. Since physiological aging induces muscle weakness via mechanisms distinct from other muscle disorders, the role of ACE2‐angiotensin 1‐7 in age‐related muscle weakness remains undetermined. Here, we investigated whether deletion of ACE2 alters the development of muscle weakness by aging and whether angiotensin 1‐7 reverses muscle weakness in older mice. Methods: After periodic measurement of grip strength and running distance in male ACE2KO and wild‐type mice until 24 months of age, we infused angiotensin 1‐7 or vehicle for 4 weeks, and measured grip strength, and excised tissues. Tissues were also excised from younger (3‐month‐old) and middle‐aged (15‐month‐old) mice. Microarray analysis of RNA was performed using tibialis anterior (TA) muscles from middle‐aged mice, and some genes were further tested using RT‐PCR. Results: Grip strength of ACE2KO mice was reduced at 6 months and was persistently lower than that of wild‐type mice ( p  < 0.01 at 6, 12, 18, and 24‐month‐old). Running distance of ACE2KO mice was shorter than that of wild‐type mice only at 24 months of age [371 ± 26 vs. 479 ± 24 (m), p  < 0.01]. Angiotensin 1‐7 improved grip strength in both types of older mice, with larger effects observed in ACE2KO mice (% increase, 3.8 ± 1.5 and 13.3 ± 3.1 in wild type and ACE2KO mice, respectively). Older, but not middle‐aged ACE2KO mice had higher oxygen consumption assessed by a metabolic cage than age‐matched wild‐type mice. Angiotensin 1‐7 infusion modestly increased oxygen consumption in older mice. There was no difference in a wheel‐running activity or glucose tolerance between ACE2KO and wild‐type mice and between mice with vehicle and angiotensin 1‐7 infusion. Analysis of TA muscles revealed that p16INK4a, a senescence‐associated gene, and central nuclei of myofibers increased in middle‐aged, but not younger ACE2KO mice. p16INK4a and central nuclei increased in TA muscles of older wild‐type mice, but the differences between ACE2KO and wild‐type mice remained significant ( p  < 0.01). Angiotensin 1‐7 did not alter the expression of p16INK4a or central nuclei in TA muscles of both types of mice. Muscle ACE2 expression of wild‐type mice was the lowest at middle age (2.6 times lower than younger age, p  < 0.05). Conclusions: Deletion of ACE2 induced the early manifestation of muscle weakness with signatures of muscle senescence. Angiotensin 1‐7 improved muscle function in older mice, supporting future application of the peptide or its analogues in the treatment of muscle weakness in the elderly population.